SUCCESSFUL PER-VAGINAL DELIVERY OF A RARE CASE OF ZIPHOPAGUS MONSTER BY EPISIOTOMY TECHNIQUE - S. Radhika; B. Chandra Prasad; M. Srinivas (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A pluriparous full-term pregnant buffalo was presented with a history of unproductive straining with improper relaxation of the vulva. Detailed obstetrical examination revealed the presence of two fetuses that were conjoined twins with attachment present at the sternal region of the thorax of the fetuses. The conjoined twins (Ziphopagus monster) were delivered per-vaginal by episiotomy technique.